Assessing Multiscale Exchange Rate Exposure of Electronic and Electrical Firms in Malaysia: An Application of Wavelet Analysis - Nurul Fathahiyah Fadhilah Mohd Azhar , Hishamuddin Abdul Wahab (International Journal of Advanced Science and Technology, 2020)
The study undertakes an in-depth study to explain cross-sectional variation of currency exposure across different time scales involving 15 electronics and electrical corporations in Malaysia from 21st July 2005 until 31st December. Past studies focused on the aggregate measurement of currency exposure which ignored the potential heterogeneity of investment holding period and created bias in estimation. To address the problem, discrete wavelet transformation (DWT) approach is employed to decompose a given time series into several frequency domains. This study finds that the level of currency exposure of the corporations exhibits heterogeneous trends across different time scales where a high level of exposure is concentrated at a higher time scale. From the findings, the study suggests that the exchange risk pricing must incorporate time scales effect in measurement and vigorous foreign exchange risk management routine should be focused primarily on widened investment interval.